2020
DOI: 10.1038/s41598-020-62087-8
|View full text |Cite
|
Sign up to set email alerts
|

The choice of anaesthesia for glioblastoma surgery does not impact the time to recurrence

Abstract: Anaesthetics used during cancer surgery may influence tumour cells and immunological response. The aim of this study was to evaluate a potential influence of the anaesthetic method (inhaled anaesthetics versus total-intravenous anaesthesia using propofol) on recurrence-free and overall survival in glioblastoma patients. We retrospectively identified patients undergoing resection of contrast enhancing glioblastoma under general anaesthesia followed by standard adjuvant treatment between January 2010 and Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The studies included 158 and 294 patients and concluded that the TIVA was not associated with any improvement in survival. 35 , 36 These studies suggest that the method of delivering general anesthetics does not influence GBM progression after surgery.…”
Section: Impact Of Anesthetics and Analgesics On Gbm Progressionmentioning
confidence: 85%
“…The studies included 158 and 294 patients and concluded that the TIVA was not associated with any improvement in survival. 35 , 36 These studies suggest that the method of delivering general anesthetics does not influence GBM progression after surgery.…”
Section: Impact Of Anesthetics and Analgesics On Gbm Progressionmentioning
confidence: 85%
“…Propofol induced apoptosis in contrast with isoflurane which increased proliferation of glioblastoma stem cells, however the results have not been consistent because of the differences induced by the cell line [29,38]. The conclusion that Grau et al have reached shows no difference between volatile agents and TIVA regarding glioblastoma recurrence (volatiles 8 vs. propofol 8,4 months) or overall survival (volatiles 16,9 vs. propofol 17,4 months) [13].…”
Section: Intravenous Agents Such As Propofol Interact Withmentioning
confidence: 96%
“…More similar studies have been published, some with overall survival at different time points as the main outcome, some studying the duration of recurrence free survival [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The number of included patients in studies with results that do not support the hypothesis [ 33 , 37 , 38 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] and studies supporting it [ 34 , 35 , 36 , 39 , 40 , 41 , 51 , 52 , 53 , 54 , 55 , 56 ], are quite equal. If anything, there are more patients in studies without support for the hypothesis.…”
Section: Retrospective Patient Studiesmentioning
confidence: 99%